2019
DOI: 10.1017/s1047951119001604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of congenital heart surgery on quality of life in children and adolescents with surgically corrected Ventricular Septal Defect, Tetralogy of Fallot, and Transposition of the Great Arteries

Abstract: Objective:To describe the impact of CHD surgery in early childhood on quality of life in children aged 10–16 years with surgically corrected Ventricular Septal Defect, Transposition of the Great Arteries, and Tetralogy of Fallot.Method:A cross-sectional survey study of quality of life survey on 161 children and adolescents aged 10–16 years with surgically corrected Ventricular Septal Defect, Transposition of the Great Arteries, and Tetralogy of Fallot. The international Paediatric Quality of Life 4.0 quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…36 We have recently investigated the quality of life in children with CHD and found that all three subgroups of CHD had decreased quality of life scores compared with healthy controls. 37 A clear association between clinical range of attentiondeficit/hyperactivity disorder symptoms load and lower quality of life scores was seen in all sub-scores in the Tetralogy of Fallot group, and to some degree a similar association was seen in the Transposition of Great Arteries group. These findings are in line with other studies 38,39 and highlight the importance of early identification and treatment of attention-deficit/hyperactivity disorder in CHD, in order to improve quality of life for these children and their families.…”
Section: Discussionmentioning
confidence: 73%
“…36 We have recently investigated the quality of life in children with CHD and found that all three subgroups of CHD had decreased quality of life scores compared with healthy controls. 37 A clear association between clinical range of attentiondeficit/hyperactivity disorder symptoms load and lower quality of life scores was seen in all sub-scores in the Tetralogy of Fallot group, and to some degree a similar association was seen in the Transposition of Great Arteries group. These findings are in line with other studies 38,39 and highlight the importance of early identification and treatment of attention-deficit/hyperactivity disorder in CHD, in order to improve quality of life for these children and their families.…”
Section: Discussionmentioning
confidence: 73%
“…According to Varni et al [ 24 ] and Huang et al [ 39 ], who identified cut-offs for patient-reported and parent-reported generic QoL, the majority of our patients (75%) and their parents (mothers: 61–80%; fathers: 74–84%) reported high levels of generic QoL, above the clinical cut-offs. These QoL levels may reflect the medical advances in screening and care for CHD in recent decades [ 40 , 41 ]. Indeed, to date, over 90% of children with a CHD are expected to survive more than 30 years after the first cardiac surgery [ 3 , 10 , 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These QoL levels may reflect the medical advances in screening and care for CHD in recent decades [ 40 , 41 ]. Indeed, to date, over 90% of children with a CHD are expected to survive more than 30 years after the first cardiac surgery [ 3 , 10 , 40 42 ]. In addition to this, our patients and their parents are involved in a multidisciplinary standardized follow-up care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the damage at school leads to single and social losses, affecting their current and future QoL. 24 …”
Section: Discussionmentioning
confidence: 99%